Degradable water-based ink and preparation method thereof
Patent Information
- Application Number
- CN202610674174.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-05-15
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2046-05-15
AI Technical Summary
为提升耐水、耐擦等性能,部分体系还会引入异氰酸酯固化剂、氮丙啶类交联剂或含钴催干剂等组分,可能带来毒性与合规压力,不利于“可降解、低风险”的发展方向
[0085]This application uses unsaturated vegetable oil as a bio-based carbon source, obtaining a cyclic carbonate precursor through epoxidation and carbon dioxide carbonation, and then constructing a non-isocyanate PHU skeleton through ring-opening polymerization with diamine. This achieves CO2 chemical fixation and material utilization while avoiding the safety and environmental risks of isocyanate systems. Furthermore, by introducing carboxyl groups through acid anhydrides and employing a bio-based dual neutralization system with arginine as the primary neutralizer and choline hydroxide as the secondary neutralizer, the resin forms an internally ionized amphiphilic structure and self-emulsifies and disperses in the aqueous phase. This reduces the odor and VOCs problems caused by traditional volatile tertiary amine neutralizers and improves the colloidal stability and batch consistency of the aqueous dispersion and ink system. Simultaneously, the PHU molecule is rich in hydroxyl/carbamate and ionized groups, which can generate multi-point adsorption and anchoring on the pigment surface, giving the resin both the function of a binder and a dispersing anchoring agent. Combined with segmented pulping, The ink release process ensures pigment refinement and stable coating while improving the manufacturability of grinding and formulation and reducing dependence on polymeric dispersants and large amounts of surfactants. In the ink formulation stage, nanocellulose is introduced to construct a reversible physical network, giving the ink shear thinning and thixotropic recovery characteristics to improve printing transfer and anti-sagging/anti-splashing performance. A cobalt-free manganese/iron drying system is used to promote the oxidation process of residual unsaturated structures under mild conditions to improve the abrasion resistance and water resistance and avoid compliance and toxicity concerns of cobalt-containing drying agents. Thus, this application achieves a comprehensive balance between sustainable properties, low odor and low volatility, stable dispersion and printability through the systematic synergy of "bio-based non-isocyanate PHU construction, bio-based double neutralization self-emulsification, resin anchoring dispersion and segmented pulping, nanocellulose rheological regulation, and cobalt-free drying enhancement".
Smart Images

Figure CN122255785B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of novel ink preparation technology, and relates to a biodegradable water-based ink and its preparation method. Background Technology
[0002] Water-based inks use water as the dispersion medium and have advantages such as low solvent content and greater safety, making them widely used in packaging, labeling, and paper-based printing. With increasing demands for green printing and carbon reduction, the market is placing higher demands on water-based inks: while ensuring printability such as transferability, thixotropic recovery, and resistance to ink splatter / sagging, further reductions in odor and VOCs are needed, along with improved raw material renewability and system biodegradability.
[0003] Currently, most water-based ink binders use water-based acrylic resins or water-based polyurethanes. Traditional water-based polyurethanes are typically produced by reacting isocyanates with polyols. Although hydrophilic groups can be introduced and neutralized with amines to form an aqueous dispersion, isocyanate raw materials pose certain safety and environmental risks. Furthermore, commonly used volatile tertiary amine neutralizers such as triethylamine can easily produce irritating odors and VOC releases, potentially causing fluctuations in storage stability. To improve water resistance and abrasion resistance, some systems also introduce isocyanate curing agents, aziridine crosslinking agents, or cobalt-containing drying agents, which may introduce toxicity and compliance pressures, hindering the development direction of "degradable and low-risk" solutions.
[0004] In addition, existing water-based inks also present contradictions in terms of pigment dispersion and rheological control: in order to obtain fine particle size and stability, they often rely on polymeric dispersants or a large amount of surfactants, which can easily lead to problems such as foaming, migration and reduced water resistance; while thickening / rheological modification can improve anti-sagging, but may affect rewetting and high-speed printing stability. Summary of the Invention
[0005] To address the aforementioned problems, the present invention aims to provide a biodegradable water-based ink and its preparation method. This application uses unsaturated vegetable oil as raw material, and prepares a non-isocyanate polyhydroxy polyurethane through epoxidation, CO2 carbonation, and diamine ring-opening polymerization. After carboxyl induction with acid anhydride, arginine is used as the primary neutralizer, and choline hydroxide as the secondary neutralizer to achieve self-emulsifying dispersion in the aqueous phase, thus achieving both bio-based properties and low odor and low VOCs from the source. The resulting polyhydroxy polyurethane (PHU) combines the functions of a binder and pigment anchoring and dispersion. Combined with segmented pulping and ink release processes, it reduces dependence on traditional dispersants and large amounts of surfactants. Simultaneously, nanocellulose is introduced to achieve shear thinning and thixotropic recovery to improve printability, and a cobalt-free manganese / iron drying system is used to improve abrasion and water resistance under mild conditions. Through the synergistic effect of these multiple processes, a comprehensive balance between sustainability, stable dispersion, and printability is achieved.
[0006] To achieve this objective, the present invention adopts the following technical solution:
[0007] In a first aspect, the present invention provides a method for preparing a biodegradable water-based ink, the method comprising:
[0008] S1: Mix unsaturated vegetable oil with organic acid, add p-toluenesulfonic acid to obtain reaction solution A, add hydrogen peroxide solution in batches, react, wash with deionized water and neutralize after the reaction is completed, dehydrate and dry under reduced pressure to obtain epoxidized oil;
[0009] S2: Epoxidized oil is mixed with a carbonation catalytic system to obtain reaction solution B. The carbonation catalytic system is a mixture of quaternary ammonium salt and Lewis acid. Carbon dioxide is introduced and the pressure is increased to react. After the reaction is completed, the temperature is reduced and the pressure is released. The mixture is washed, filtered, and de-vaporized under reduced pressure to obtain a cyclic carbonate precursor.
[0010] S3: A cyclic carbonate precursor, diamine A and diamine B are mixed to obtain reaction solution C, and the reaction yields PHU prepolymer; acid anhydride, catalyst and antioxidant are added to obtain reaction solution D, and the reaction is stirred to obtain carboxyl-modified PHU;
[0011] S4: Arginine solution is added to carboxyl-modified PHU for primary neutralization, followed by choline hydroxide solution for secondary neutralization to obtain a neutralized solution. Deionized water is added and sheared to obtain a dispersion. The pH of the dispersion is adjusted by adding a small amount of arginine solution / choline solution or deionized water, and the solid content is adjusted to obtain an aqueous PHU dispersion.
[0012] S5: Add pigment to part of PHU aqueous dispersion, add wetting agent alkyl glycoside and defoamer to obtain color paste, add deionized water to obtain second color paste, and use sand mill to grind and disperse to obtain concentrated color paste;
[0013] S6: Mix the concentrated color paste with the remaining PHU aqueous dispersion, add nanocellulose dispersion, humectant, wetting agent, preservative and defoamer to obtain ink, add cobalt-free manganese / iron drier, stir to obtain second ink, adjust pH and solid content to obtain biodegradable water-based ink.
[0014] As a preferred technical solution of the present invention, in step S1, the unsaturated vegetable oil is any one of soybean oil, flaxseed oil, and rapeseed oil;
[0015] The organic acid is formic acid or acetic acid;
[0016] In some optional embodiments, the mass ratio of the unsaturated vegetable oil to the organic acid is 1:(0.05-0.1), for example, it can be 1:0.050, 1:0.055, 1:0.060, 1:0.065, 1:0.070, 1:0.075, 1:0.080, 1:0.085, 1:0.090, 1:0.095 or 1:0.100, but is not limited to the listed values, other unlisted values within this range are also applicable.
[0017] In some optional embodiments, the amount of p-toluenesulfonic acid fed is 0.1-0.8 wt.% of the mass of the unsaturated vegetable oil, for example, it can be 0.10 wt.%, 0.17 wt.%, 0.24 wt.%, 0.31 wt.%, 0.38 wt.%, 0.45 wt.%, 0.52 wt.%, 0.59 wt.%, 0.66 wt.%, 0.73 wt.%, or 0.80 wt.%, but is not limited to the listed values, and other unlisted values within this range are also applicable.
[0018] In some optional embodiments, the mass fraction of the hydrogen peroxide solution is 30-50 wt.%, for example, it can be 30 wt.%, 32 wt.%, 34 wt.%, 36 wt.%, 38 wt.%, 40 wt.%, 42 wt.%, 44 wt.%, 46 wt.%, 48 wt.%, or 50 wt.%, but is not limited to the listed values; other unlisted values within this range are also applicable.
[0019] In some optional embodiments, the mass ratio of the hydrogen peroxide solution to the unsaturated vegetable oil is (0.15-0.45):1, for example, it can be 0.15:1, 0.18:1, 0.21:1, 0.24:1, 0.27:1, 0.30:1, 0.33:1, 0.36:1, 0.39:1, 0.42:1 or 0.45:1, but is not limited to the listed values, other unlisted values within this range are also applicable.
[0020] In some alternative embodiments, the reaction temperature is 45-70°C, for example, 45.0°C, 47.5°C, 50.0°C, 52.5°C, 55.0°C, 57.5°C, 60.0°C, 62.5°C, 65.0°C, 67.5°C, or 70.0°C, but is not limited to the listed values; other unlisted values within this range are also applicable.
[0021] In some alternative embodiments, the reaction time is 3-8 hours, for example, 3.0 hours, 3.5 hours, 4.0 hours, 4.5 hours, 5.0 hours, 5.5 hours, 6.0 hours, 6.5 hours, 7.0 hours, 7.5 hours, or 8.0 hours, but is not limited to the listed values; other unlisted values within this range are also applicable.
[0022] In some optional embodiments, after the reaction is completed, the solution is washed with deionized water and neutralized to a pH of 6.0-8.0, such as 6.0, 6.2, 6.4, 6.6, 6.8, 7.0, 7.2, 7.4, 7.6, 7.8 or 8.0, but not limited to the listed values; other unlisted values within this range are also applicable.
[0023] As a preferred embodiment of the present invention, in step S2, the mass ratio of quaternary ammonium salt to Lewis acid in the carbonation catalytic system is (15-20):1, for example, it can be 15.0:1, 15.5:1, 16.0:1, 16.5:1, 17.0:1, 17.5:1, 18.0:1, 18.5:1, 19.0:1, 19.5:1 or 20.0:1, but is not limited to the listed values, other unlisted values within this range are also applicable.
[0024] The quaternary ammonium salt is any one of tetrabutylammonium bromide, tetrabutylammonium chloride, tetrabutylammonium iodide, and tetraethylammonium bromide.
[0025] The Lewis acid is any one of zinc bromide, zinc chloride, and magnesium bromide.
[0026] In some optional embodiments, the amount of the carbonation catalytic system fed is 1-3% of the mass of the epoxidized oil, for example, it can be 1.0%, 1.2%, 1.4%, 1.6%, 1.8%, 2.0%, 2.2%, 2.4%, 2.6%, 2.8% or 3.0%, but is not limited to the listed values, and other unlisted values within this range are also applicable.
[0027] In some alternative embodiments, the reaction pressure is 0.5-3.5 MPa, for example, 0.5 MPa, 0.8 MPa, 1.1 MPa, 1.4 MPa, 1.7 MPa, 2.0 MPa, 2.3 MPa, 2.6 MPa, 2.9 MPa, 3.2 MPa or 3.5 MPa, but is not limited to the listed values; other unlisted values within this range are also applicable.
[0028] In some optional embodiments, the reaction temperature of the reaction solution B is 80-130°C, for example, it can be 80°C, 85°C, 90°C, 95°C, 100°C, 105°C, 110°C, 115°C, 120°C, 125°C or 130°C, but is not limited to the listed values, other unlisted values within this range are also applicable.
[0029] In some optional embodiments, the reaction time of the reaction solution B is 4-12 hours, for example, 4.0 hours, 4.8 hours, 5.6 hours, 6.4 hours, 7.2 hours, 8.0 hours, 8.8 hours, 9.6 hours, 10.4 hours, 11.2 hours or 12.0 hours, but is not limited to the listed values. Other unlisted values within this range are also applicable.
[0030] As a preferred technical solution of the present invention, in step S3, the diamine A is any one of 1,4-butanediamine, 1,5-pentanediamine, and 1,6-hexanediamine.
[0031] The diamine B is any one of 1,8-diamino-3,6-dioxane, bis(3-aminopropyl) ether, or PEG-diamine.
[0032] In some optional embodiments, the molar ratio of diamine A to diamine B is (1-9):1, for example, it can be 1.0:1, 1.8:1, 2.6:1, 3.4:1, 4.2:1, 5.0:1, 5.8:1, 6.6:1, 7.4:1, 8.2:1 or 9.0:1, but is not limited to the listed values, other unlisted values within this range are also applicable.
[0033] In some optional embodiments, the total amount of diamine A and diamine B fed to the cyclic carbonate precursor is in a mass ratio of (8-25):100, for example, 8.0:100, 9.7:100, 11.4:100, 13.1:100, 14.8:100, 16.5:100, 18.2:100, 19.9:100, 21.6:100, 23.3:100 or 25.0:100, but is not limited to the listed values; other unlisted values within this range are also applicable.
[0034] In some optional embodiments, the reaction temperature of the reaction solution C is 50-95°C, for example, it can be 50.0°C, 54.5°C, 59.0°C, 63.5°C, 68.0°C, 72.5°C, 77.0°C, 81.5°C, 86.0°C, 90.5°C or 95.0°C, but is not limited to the listed values, other unlisted values within this range are also applicable.
[0035] In some optional embodiments, the reaction time of the reaction solution C is 6-24h, for example, it can be 6.0h, 7.8h, 9.6h, 11.4h, 13.2h, 15.0h, 16.8h, 18.6h, 20.4h, 22.2h or 24.0h, but is not limited to the listed values, other unlisted values within this range are also applicable.
[0036] The acid anhydride is any one or more of succinic anhydride, itaconic anhydride, and maleic anhydride.
[0037] In some optional embodiments, the mass ratio of the anhydride to the PHU prepolymer is (2-20):100, for example, it can be 2:100, 3.8:100, 5.6:100, 7.4:100, 9.2:100, 11.0:100, 12.8:100, 14.6:100, 16.4:100, 18.2:100 or 20.0:100, but is not limited to the listed values, other unlisted values within this range are also applicable.
[0038] The catalyst is any one of imidazole, 1-methylimidazolium, 4-dimethylaminopyridine, or pyridine.
[0039] In some optional embodiments, the amount of catalyst fed is 0.1-0.5% of the mass of the PHU prepolymer, for example, it can be 0.10%, 0.14%, 0.18%, 0.22%, 0.26%, 0.30%, 0.34%, 0.38%, 0.42%, 0.46% or 0.50%, but is not limited to the listed values, other unlisted values within this range are also applicable.
[0040] In some optional embodiments, the antioxidant is any one of 2,6-di-tert-butyl-p-cresol, Irganox 1010, and Irganox 1076.
[0041] In some optional embodiments, the amount of antioxidant added is 0.05-0.2% of the mass of PHU prepolymer, for example, it can be 0.050%, 0.065%, 0.080%, 0.095%, 0.110%, 0.125%, 0.140%, 0.155%, 0.170%, 0.185% or 0.200%, but is not limited to the listed values, other unlisted values within this range are also applicable.
[0042] In some optional embodiments, the temperature of the reaction mixture D during stirring is 60-110°C, for example, it can be 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C, 100°C, 105°C or 110°C, but is not limited to the listed values, other unlisted values within this range are also applicable.
[0043] In some optional embodiments, the reaction time of the reaction solution D is 2-8 hours, for example, it can be 2.0 hours, 2.6 hours, 3.2 hours, 3.8 hours, 4.4 hours, 5.0 hours, 5.6 hours, 6.2 hours, 6.8 hours, 7.4 hours or 8.0 hours, but is not limited to the listed values. Other unlisted values within this range are also applicable.
[0044] As a preferred technical solution of the present invention, in step S4, the concentration of the arginine solution is 0.1-0.5M, for example, it can be 0.10M, 0.14M, 0.18M, 0.22M, 0.26M, 0.30M, 0.34M, 0.38M, 0.42M, 0.46M or 0.50M, but is not limited to the listed values. Other unlisted values within this range are also applicable.
[0045] In some optional embodiments, the mass ratio of arginine to carboxyl-modified PHU is (1-6):100, for example, it can be 1.0:100, 1.5:100, 2.0:100, 2.5:100, 3.0:100, 3.5:100, 4.0:100, 4.5:100, 5.0:100, 5.5:100 or 6.0:100, but is not limited to the listed values, other unlisted values within this range are also applicable.
[0046] In some alternative embodiments, the concentration of the choline hydroxide solution is 0.1-0.5M, for example, 0.10M, 0.14M, 0.18M, 0.22M, 0.26M, 0.30M, 0.34M, 0.38M, 0.42M, 0.46M or 0.50M, but is not limited to the listed values; other unlisted values within this range are also applicable.
[0047] In some optional embodiments, the mass ratio of choline hydroxide to carboxyl-modified PHU is (1-2):100, for example, it can be 1.0:100, 1.1:100, 1.2:100, 1.3:100, 1.4:100, 1.5:100, 1.6:100, 1.7:100, 1.8:100, 1.9:100 or 2.0:100, but is not limited to the listed values, other unlisted values within this range are also applicable.
[0048] In some optional embodiments, the shear dispersion time is 30-60 min, for example, it can be 30 min, 33 min, 36 min, 39 min, 42 min, 45 min, 48 min, 51 min, 54 min, 57 min or 60 min, but is not limited to the listed values, other unlisted values within this range are also applicable.
[0049] In some optional embodiments, the mass ratio of the deionized water to the carboxyl-modified PHU is (1-3):1, for example, it can be 1.0:1, 1.2:1, 1.4:1, 1.6:1, 1.8:1, 2.0:1, 2.2:1, 2.4:1, 2.6:1, 2.8:1 or 3.0:1, but is not limited to the listed values, other unlisted values within this range are also applicable.
[0050] In some optional embodiments, the rotational speed of the shear dispersion is 5000-8000 rpm, for example, it can be 5000 rpm, 5300 rpm, 5600 rpm, 5900 rpm, 6200 rpm, 6500 rpm, 6800 rpm, 7100 rpm, 7400 rpm, 7700 rpm or 8000 rpm, but is not limited to the listed values, other unlisted values within this range are also applicable.
[0051] In some alternative embodiments, the pH of the dispersion is adjusted by adding a small amount of arginine / choline solution or deionized water.
[0052] In some alternative embodiments, the pH of the adjusted dispersion is 8.0-9.2, for example, 8.00, 8.12, 8.24, 8.36, 8.48, 8.60, 8.72, 8.84, 8.96, 9.08 or 9.20, but is not limited to the listed values; other unlisted values within this range are also applicable.
[0053] In some optional embodiments, the solid content of the PHU aqueous dispersion is 30-40 wt.%, for example, it can be 30 wt.%, 31 wt.%, 32 wt.%, 33 wt.%, 34 wt.%, 35 wt.%, 36 wt.%, 37 wt.%, 38 wt.%, 39 wt.%, or 40 wt.%, but is not limited to the listed values, and other unlisted values within this range are also applicable.
[0054] As a preferred technical solution of the present invention, in step S5, the mass ratio of the pigment to the PHU resin solid in the PHU aqueous dispersion is (20:80-40:60), for example, it can be 20:80, 22:78, 24:76, 26:74, 28:72, 30:70, 32:68, 34:66, 36:64, 38:62 or 40:60, but it is not limited to the listed values. Other unlisted values within this range are also applicable.
[0055] In some optional embodiments, the amount of the PHU aqueous dispersion accounts for 30-60% of the total amount of PHU aqueous dispersion, for example, it can be 30%, 33%, 36%, 39%, 42%, 45%, 48%, 51%, 54%, 57% or 60%, but is not limited to the listed values, and other unlisted values within this range are also applicable.
[0056] In some optional embodiments, the amount of the wetting agent alkyl glycoside is 0.1-0.3 wt.% of the total amount of pigment paste, for example, it can be 0.10 wt.%, 0.12 wt.%, 0.14 wt.%, 0.16 wt.%, 0.18 wt.%, 0.20 wt.%, 0.22 wt.%, 0.24 wt.%, 0.26 wt.%, 0.28 wt.% or 0.30 wt.%, but is not limited to the listed values, other unlisted values within this range are also applicable.
[0057] The defoamer is either TEGO® Foamex 832 or SURFYNOL® DF-62.
[0058] In some optional embodiments, the amount of defoamer added is 0.1-0.3 wt.% of the total amount of pigment paste, for example, it can be 0.10 wt.%, 0.12 wt.%, 0.14 wt.%, 0.16 wt.%, 0.18 wt.%, 0.20 wt.%, 0.22 wt.%, 0.24 wt.%, 0.26 wt.%, 0.28 wt.% or 0.30 wt.%, but is not limited to the listed values, other unlisted values within this range are also applicable.
[0059] In some optional embodiments, the solid content of the second color paste is 30-60 wt.%, for example, it can be 30 wt.%, 33 wt.%, 36 wt.%, 39 wt.%, 42 wt.%, 45 wt.%, 48 wt.%, 51 wt.%, 54 wt.%, 57 wt.%, or 60 wt.%, but is not limited to the listed values, and other unlisted values within this range are also applicable.
[0060] In some optional embodiments, the grinding and dispersion time is 0.5-2.5h, for example, it can be 0.5h, 0.7h, 0.9h, 1.1h, 1.3h, 1.5h, 1.7h, 1.9h, 2.1h, 2.3h or 2.5h, but is not limited to the listed values, other unlisted values within this range are also applicable.
[0061] In some optional embodiments, the particle size of the grinding media is 0.2-1 mm, for example, it can be 0.20 mm, 0.28 mm, 0.36 mm, 0.44 mm, 0.52 mm, 0.60 mm, 0.68 mm, 0.76 mm, 0.84 mm, 0.92 mm or 1.00 mm, but is not limited to the listed values, other unlisted values within this range are also applicable.
[0062] In some optional embodiments, the grinding temperature is 35-45°C, for example, it can be 35°C, 36°C, 37°C, 38°C, 39°C, 40°C, 41°C, 42°C, 43°C, 44°C or 45°C, but is not limited to the listed values, other unlisted values within this range are also applicable.
[0063] As a preferred technical solution of the present invention, in step S6, the mass fraction of nanocellulose in the ink is 0.1-0.6 wt.%, for example, it can be 0.10 wt.%, 0.15 wt.%, 0.20 wt.%, 0.25 wt.%, 0.30 wt.%, 0.35 wt.%, 0.40 wt.%, 0.45 wt.%, 0.50 wt.%, 0.55 wt.%, or 0.60 wt.%, but it is not limited to the listed values. Other unlisted values within this range are also applicable.
[0064] The moisturizer is any one of glycerin, sorbitol, and propylene glycol.
[0065] In some optional embodiments, the mass fraction of the humectant in the ink is 2-12 wt.%, for example, it can be 2 wt.%, 3 wt.%, 4 wt.%, 5 wt.%, 6 wt.%, 7 wt.%, 8 wt.%, 9 wt.%, 10 wt.%, 11 wt.%, or 12 wt.%, but is not limited to the listed values, and other unlisted values within this range are also applicable.
[0066] In some optional embodiments, the wetting agent in the ink has a mass fraction of 0.1-0.2 wt.%, for example, it may be 0.10 wt.%, 0.11 wt.%, 0.12 wt.%, 0.13 wt.%, 0.14 wt.%, 0.15 wt.%, 0.16 wt.%, 0.17 wt.%, 0.18 wt.%, 0.19 wt.%, or 0.20 wt.%, but is not limited to the listed values; other unlisted values within this range are also applicable.
[0067] The preservative is 1,2-benzisothiazolin-3-one or methylisothiazolinone.
[0068] In some optional embodiments, the preservative in the ink has a mass fraction of 0.01-0.1 wt.%, for example, it may be 0.010 wt.%, 0.019 wt.%, 0.028 wt.%, 0.037 wt.%, 0.046 wt.%, 0.055 wt.%, 0.064 wt.%, 0.073 wt.%, 0.082 wt.%, 0.091 wt.%, or 0.100 wt.%, but is not limited to the listed values; other unlisted values within this range are also applicable.
[0069] In some optional embodiments, the defoamer in the ink has a mass fraction of 0.1-0.3 wt.%, for example, it may be 0.10 wt.%, 0.12 wt.%, 0.14 wt.%, 0.16 wt.%, 0.18 wt.%, 0.20 wt.%, 0.22 wt.%, 0.24 wt.%, 0.26 wt.%, 0.28 wt.%, or 0.30 wt.%, but is not limited to the listed values; other unlisted values within this range are also applicable.
[0070] In some optional embodiments, the amount of the cobalt-free manganese / iron drier is 0.1-0.5% of the ink mass, for example, it can be 0.10%, 0.14%, 0.18%, 0.22%, 0.26%, 0.30%, 0.34%, 0.38%, 0.42%, 0.46% or 0.50%, but is not limited to the listed values, other unlisted values within this range are also applicable.
[0071] In some alternative embodiments, the stirring temperature is 20-40°C, for example, 20°C, 22°C, 24°C, 26°C, 28°C, 30°C, 32°C, 34°C, 36°C, 38°C or 40°C, but is not limited to the listed values, and other unlisted values within this range are also applicable.
[0072] In some optional embodiments, the stirring time is 10-40 min, for example, it can be 10 min, 13 min, 16 min, 19 min, 22 min, 25 min, 28 min, 31 min, 34 min, 37 min or 40 min, but is not limited to the listed values, other unlisted values within this range are also applicable.
[0073] In some alternative embodiments, the pH of the biodegradable water-based ink is 8-9.2, for example, it can be 8.00, 8.12, 8.24, 8.36, 8.48, 8.60, 8.72, 8.84, 8.96, 9.08 or 9.20, but is not limited to the listed values, other unlisted values within this range are also applicable.
[0074] In some optional embodiments, the solid content of the biodegradable water-based ink is 20-40 wt.%, for example, it can be 20 wt.%, 22 wt.%, 24 wt.%, 26 wt.%, 28 wt.%, 30 wt.%, 32 wt.%, 34 wt.%, 36 wt.%, 38 wt.%, or 40 wt.%, but is not limited to the listed values; other unlisted values within this range are also applicable.
[0075] Secondly, the present invention provides a biodegradable water-based ink prepared by the preparation method described above.
[0076] This application uses unsaturated vegetable oil as a bio-based carbon source and constructs a PHU framework via a non-isocyanate route of "epoxidation, CO2 carbonation, and diamine ring-opening polymerization." Building upon this, it introduces a strategy of "anhydride-induced carboxylation, arginine-based neutralization / choline hydroxide-assisted neutralization, and aqueous self-emulsification dispersion," enabling the resulting resin to possess both biodegradable framework characteristics and the colloidal stability and printability required for water-based inks. This application, through the combination of bio-based raw material sources, CO2 fixation and conversion, and a bio-based dual neutralization system, forms differentiated structural units and colloidal stabilization mechanisms, reducing isocyanate-related safety and odor / VOC risks, and providing a more controllable basis for interfacial interactions and rheological regulation in ink systems.
[0077] In the epoxidation step, the carbon-carbon double bonds of unsaturated vegetable oils are epoxidized under acidic conditions by reacting with a peracidic system formed by hydrogen peroxide. The double bonds are converted into epoxy groups, constructing active sites that can subsequently undergo carbonation reactions with CO2. The batch addition of hydrogen peroxide reduces the exothermic peak of the system and inhibits the ring-opening side reactions of the epoxy in the presence of acid / water, ensuring more effective retention of the epoxidized sites and thus improving the subsequent carbonation efficiency and the controllability of the resin structure.
[0078] In the carbonation step, epoxidized oil reacts with carbon dioxide under the synergistic catalysis of quaternary ammonium salt and Lewis acid to form a five-membered cyclic carbonate structure. The halide ions provided by the quaternary ammonium salt have a ring-opening activation effect on the epoxy group, while the Lewis acid enhances the electrophilicity of the epoxidized carbon through coordination and lowers the reaction energy barrier, allowing CO2 to be efficiently fixed into the molecular structure within a relatively mild temperature and pressure window, forming a cyclic carbonate precursor capable of undergoing aminolytic ring-opening polymerization. This step not only achieves the chemical fixation of CO2 but also transforms bio-based oils from low-reactivity hydrophobic molecules into controllably polymerizable active monomer precursors.
[0079] In the PHU construction and carboxyl introduction steps, a cyclic carbonate precursor undergoes a ring-opening addition reaction with a diamine to generate a PHU structural unit containing urethane bonds and rich in hydroxyl groups. Diamine A provides aliphatic segments to support mechanical strength and durability, while diamine B introduces ether chain flexibility and hydrophilicity to improve low-temperature toughness and water dispersion compatibility. The hydroxyl groups and urethane groups in the PHU system can form a multi-point hydrogen bond network, providing intrinsic sites for subsequent pigment anchoring, rheological construction, and dispersion stabilization. Subsequently, carboxyl side groups are introduced through ring-opening esterification / semi-esterification reactions between acid anhydrides and the hydroxyl groups in the PHU, giving the resin built-in hydrophilic groups capable of neutralizing ionization. A catalyst promotes the efficiency of anhydride ring-opening and esterification, while an antioxidant reduces the risk of oxidative discoloration and viscosity drift during high-temperature stirring. This step forms a hydroxyl-rich PHU skeleton via a non-isocyanate route and introduces ionizable carboxyl sites through acid anhydrides, providing the structural prerequisite for subsequent self-emulsifying water dispersion.
[0080] In the bio-based dual neutralization and self-emulsifying dispersion step, this application uses arginine solution for primary neutralization and choline hydroxide solution for secondary neutralization, converting carboxyl groups into corresponding ion-pair structures. This allows the carboxyl-modified PHU to form an amphiphilic structure consisting of a hydrophobic backbone and ionized side groups, forming stable colloidal particles in the aqueous phase. Arginine, as an amino acid-type neutralizing agent, can introduce multi-site hydrogen bond donors and acceptors and a hydration layer while providing ionization, enhancing colloidal stability. Choline hydroxide, as a low-volatility, renewable alkaline system, can supplement neutralization capacity and improve dispersion formation efficiency. Unlike the neutralization of volatile tertiary amines such as triethylamine, the dual neutralization system of this application not only reduces odor and volatility risks but also makes it easier to achieve a controllable window for particle size and storage stability through the synergistic stabilization mechanism of amino acid ion pairs and hydroxyl / carbamate hydrogen bond networks.
[0081] This application uses a portion of PHU aqueous dispersion as a grinding carrier for segmented pulping. During the sand milling process, as the pigment is sheared and depolymerized, creating a fresh surface, PHU molecules adsorb and anchor at multiple points on the pigment surface through hydroxyl groups, carbamates, and ionized groups, thus achieving the function of both resin and dispersant / anchoring agent. Alkyl glycoside wetting agents lower the wetting and water entry barriers in the aqueous phase, improving grinding efficiency and reducing reliance on traditional polymeric dispersants or large amounts of surfactants. Defoamers control microbubbles introduced during grinding, reducing stability fluctuations caused by foam entrainment. Through a process structure of partial resin pulping followed by ink release, it is possible to ensure particle size refinement and anchoring stability while avoiding excessively high system viscosity that could affect grinding efficiency. This makes the coupling between pigment dispersion, resin adsorption, and subsequent formulation adjustments more controllable.
[0082] In the ink formulation and rheological construction steps, concentrated pigment paste is mixed with the remaining PHU aqueous dispersion and then a nanocellulose dispersion is added. The nanocellulose forms a reversible physical network in the aqueous phase, primarily based on hydrogen bonds, providing shear thinning and thixotropic recovery behavior. This meets the rheological requirements of low viscosity for easy transfer on the printing press and rapid recovery after printing to prevent sagging / ink splatter. A humectant improves open time and rewetting by reducing the rate of water evaporation and regulating water activity. A preservative inhibits microbial growth during storage of the aqueous system to improve shelf stability. An antifoaming agent controls air bubbles during ink mixing and reduces printing defects. The cobalt-manganese / iron-free drying system promotes a mild oxidation process of residual unsaturated structures in the system under air conditions, tending to improve the ink system's abrasion and water resistance without relying on highly toxic crosslinking agents or isocyanate curing agents.
[0083] This application also features a multi-stage synergistic effect: At the front end, renewable raw materials and carbon dioxide fixation are introduced into the resin structure through vegetable oil, epoxidation, and CO2 carbonation, giving the PHU skeleton a structural unit distinct from conventional waterborne resins; in the middle stage, anhydride-induced carboxyl groups and arginine / choline hydroxide double neutralization construct a low-volatility, bio-based built-in ionization and hydrogen bonding synergistic stabilization mechanism, resulting in a more stable and adjustable window for the aqueous dispersion; at the back end, resin anchoring dispersion, segmented pulping and ink release, and nanocellulose rheological networks achieve interface stability, particle size control, and printing rheology, reducing dependence on polymeric dispersants and highly toxic crosslinking agents; finally, a cobalt-free manganese / iron drying system is used to achieve performance enhancement under mild conditions. Thus, resin construction, dispersion stabilization, rheological regulation, and performance maintenance are synergistically achieved, resulting in a biodegradable waterborne ink with comprehensive effects including renewable sources / CO2 fixation, low volatility neutralization, stable dispersion, good printability, and environmental friendliness.
[0084] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0085] This application uses unsaturated vegetable oil as a bio-based carbon source, obtaining a cyclic carbonate precursor through epoxidation and carbon dioxide carbonation, and then constructing a non-isocyanate PHU skeleton through ring-opening polymerization with diamine. This achieves CO2 chemical fixation and material utilization while avoiding the safety and environmental risks of isocyanate systems. Furthermore, by introducing carboxyl groups through acid anhydrides and employing a bio-based dual neutralization system with arginine as the primary neutralizer and choline hydroxide as the secondary neutralizer, the resin forms an internally ionized amphiphilic structure and self-emulsifies and disperses in the aqueous phase. This reduces the odor and VOCs problems caused by traditional volatile tertiary amine neutralizers and improves the colloidal stability and batch consistency of the aqueous dispersion and ink system. Simultaneously, the PHU molecule is rich in hydroxyl / carbamate and ionized groups, which can generate multi-point adsorption and anchoring on the pigment surface, giving the resin both the function of a binder and a dispersing anchoring agent. Combined with segmented pulping, The ink release process ensures pigment refinement and stable coating while improving the manufacturability of grinding and formulation and reducing dependence on polymeric dispersants and large amounts of surfactants. In the ink formulation stage, nanocellulose is introduced to construct a reversible physical network, giving the ink shear thinning and thixotropic recovery characteristics to improve printing transfer and anti-sagging / anti-splashing performance. A cobalt-free manganese / iron drying system is used to promote the oxidation process of residual unsaturated structures under mild conditions to improve the abrasion resistance and water resistance and avoid compliance and toxicity concerns of cobalt-containing drying agents. Thus, this application achieves a comprehensive balance between sustainable properties, low odor and low volatility, stable dispersion and printability through the systematic synergy of "bio-based non-isocyanate PHU construction, bio-based double neutralization self-emulsification, resin anchoring dispersion and segmented pulping, nanocellulose rheological regulation, and cobalt-free drying enhancement". Attached Figure Description
[0086] Figure 1 This is a physical image of the biodegradable water-based ink prepared in Example 1 of this application. Detailed Implementation
[0087] The technical solutions of the present invention will be described in detail below with reference to specific embodiments and accompanying drawings. The embodiments described herein are specific implementations of the present invention, used to illustrate the concept of the present invention; these descriptions are explanatory and exemplary, and should not be construed as limiting the implementation methods or the scope of protection of the present invention. In addition to the embodiments described herein, those skilled in the art can employ other obvious technical solutions based on the content disclosed in the claims and specification of this application. These technical solutions include any obvious substitutions and modifications made to the embodiments described herein.
[0088] The chemical reagents used in the embodiments and comparative examples of this invention are all commercially available products and have not undergone further purification or processing.
[0089] Example 1
[0090] This embodiment provides a biodegradable water-based ink and its preparation method, the preparation method specifically including the following steps:
[0091] S1: Unsaturated vegetable oil soybean oil and organic acid formic acid are mixed at a mass ratio of 1:0.08. P-toluenesulfonic acid is added to obtain reaction solution A, wherein the amount of p-toluenesulfonic acid added is 0.6 wt.% of the mass of unsaturated vegetable oil. Hydrogen peroxide solution with a mass fraction of 45 wt.% is added in batches, wherein the mass ratio of hydrogen peroxide solution to unsaturated vegetable oil is 0.35:1. The reaction is carried out at 65℃ for 7 hours. After the reaction is completed, the mixture is washed with deionized water and neutralized to a pH of 7.5. The mixture is then dehydrated under reduced pressure and dried to obtain epoxidized oil.
[0092] S2: Epoxidized oil is mixed with a carbonation catalytic system to obtain reaction solution B. The carbonation catalytic system is a mixture of tetrabutylammonium bromide and zinc bromide in Lewis acid at a mass ratio of 18:1. The amount of carbonation catalytic system is 2.5% of the mass of epoxidized oil. Carbon dioxide is introduced and the pressure is increased to 2.5 MPa. The reaction is carried out at 110°C for 10 h. After the reaction is completed, the temperature is reduced and the pressure is released. The product is washed, filtered, and subjected to vacuum devolatilization to obtain a cyclic carbonate precursor.
[0093] S3: A reaction solution C is prepared by mixing a cyclic carbonate precursor, diamine A (1,4-butanediamine), and diamine B (1,8-diamino-3,6-dioxane), wherein the molar ratio of diamine A to diamine B is 8:1, and the total amount of diamine A and diamine B is in a mass ratio of 20:100 to the cyclic carbonate precursor. The mixture is reacted at 80°C for 20 h to obtain a PHU prepolymer. A reaction solution D is prepared by adding an acid anhydride (succinic anhydride), a catalyst (imidazolium), and an antioxidant (2,6-di-tert-butyl-p-cresol), wherein the mass ratio of the acid anhydride to the PHU prepolymer is 15:100, the amount of catalyst is 0.4% of the mass of the PHU prepolymer, and the amount of antioxidant is 0.15% of the mass of the PHU prepolymer. The mixture is stirred at 100°C for 6 h to obtain a carboxyl-modified PHU.
[0094] S4: Add a 0.4M arginine solution to the carboxyl-modified PHU for primary neutralization, wherein the mass ratio of arginine to carboxyl-modified PHU is 5:100. Then add a 0.4M choline hydroxide solution for secondary neutralization to obtain a neutralized solution, wherein the mass ratio of choline hydroxide to carboxyl-modified PHU is 1.8:100. Add deionized water and shear disperse for 50 min to obtain a dispersion, wherein the mass ratio of deionized water to carboxyl-modified PHU is 2.5:1 and the shearing speed is 7500 rpm. Adjust the pH of the dispersion to 9.0 and adjust the solid content to obtain a PHU aqueous dispersion with a solid content of 38 wt.%.
[0095] S5: Add pigment to a portion of the PHU aqueous dispersion, wherein the mass ratio of pigment to PHU resin solids in the portion of the PHU aqueous dispersion is 35:65, and the amount of the portion of PHU aqueous dispersion accounts for 55% of the total amount of PHU aqueous dispersion. Add wetting agent alkyl glycoside and defoamer TEGO® Foamex 832 to obtain a color paste, wherein the amount of wetting agent added is 0.25 wt.% of the total amount of color paste, and the amount of defoamer added is 0.2 wt.% of the total amount of color paste. Add deionized water to obtain a second color paste with a solid content of 50 wt.%. Grind and disperse using a sand mill for 2.0 h to obtain a concentrated color paste; wherein the particle size of the grinding media is 0.8 mm, and the grinding temperature is 42℃.
[0096] S6: Mix the concentrated color paste with the remaining PHU aqueous dispersion, add nanocellulose dispersion, glycerin (a humectant), wetting agent, 1,2-benzisothiazolin-3-one (a preservative), and defoamer to obtain ink, wherein the mass fraction of nanocellulose is 0.5 wt.%, the mass fraction of humectant is 10 wt.%, the mass fraction of wetting agent is 0.18 wt.%, the mass fraction of preservative is 0.08 wt.%, and the mass fraction of defoamer is 0.25 wt.%. Add cobalt-free manganese / iron drier, wherein the amount of cobalt-free manganese / iron drier is 0.4% of the ink mass. Stir at 35°C for 30 min to obtain the second ink. Adjust the pH to 9.0 and the solid content to 35 wt.% to obtain the biodegradable water-based ink. Figure 1 The photograph shows the actual product of the biodegradable water-based ink prepared in this embodiment. It can be seen that the ink is in a uniformly dispersed state, with no obvious layering or sedimentation, and no obvious continuous foam on the surface.
[0097] Example 2
[0098] This embodiment provides a biodegradable water-based ink and its preparation method. The preparation method of the biodegradable water-based ink specifically includes the following steps:
[0099] S1: Unsaturated vegetable oil linseed oil and organic acid formic acid were mixed at a mass ratio of 1:0.05. P-toluenesulfonic acid was added to obtain reaction solution A, wherein the amount of p-toluenesulfonic acid added was 0.1 wt.% of the mass of unsaturated vegetable oil. Hydrogen peroxide solution with a mass fraction of 30 wt.% was added in batches, wherein the mass ratio of hydrogen peroxide solution to unsaturated vegetable oil was 0.15:1. The reaction was carried out at 45℃ for 3 hours. After the reaction was completed, the mixture was washed with deionized water and neutralized to a pH of 6.0. The mixture was then dehydrated under reduced pressure and dried to obtain epoxidized oil.
[0100] S2: Epoxidized oil is mixed with a carbonation catalytic system to obtain reaction solution B. The carbonation catalytic system is a mixture of tetrabutylammonium chloride and zinc chloride of Lewis acid at a mass ratio of 20:1. The amount of carbonation catalytic system fed is 1% of the mass of epoxidized oil. Carbon dioxide is introduced and the pressure is increased to 0.5 MPa. The reaction is carried out at 80°C for 4 hours. After the reaction is completed, the temperature is reduced and the pressure is released. The product is washed, filtered, and subjected to vacuum devolatilization to obtain a cyclic carbonate precursor.
[0101] S3: A reaction solution C is prepared by mixing a cyclic carbonate precursor, diamine A (1,5-pentanediamine), and diamine B (bis(3-aminopropyl) ether), wherein the molar ratio of diamine A to diamine B is 1:1, and the total amount of diamine A and diamine B is in a mass ratio of 8:100 to the cyclic carbonate precursor. The reaction is carried out at 50°C for 6 hours to obtain a PHU prepolymer. An acid anhydride (itaconic anhydride), a catalyst (1-methylimidazole), and an antioxidant (Irganox 1010) are added to obtain a reaction solution D, wherein the mass ratio of acid anhydride to PHU prepolymer is 2:100, the amount of catalyst is 0.1% of the mass of PHU prepolymer, and the amount of antioxidant is 0.05% of the mass of PHU prepolymer. The reaction is carried out at 60°C for 2 hours with stirring to obtain a carboxyl-modified PHU.
[0102] S4: Add a 0.1M arginine solution to the carboxyl-modified PHU for primary neutralization, wherein the mass ratio of arginine to carboxyl-modified PHU is 1:100. Then add a 0.1M choline hydroxide solution for secondary neutralization to obtain a neutralized solution, wherein the mass ratio of choline hydroxide to carboxyl-modified PHU is 1:100. Add deionized water and shear disperse for 30 min to obtain a dispersion, wherein the mass ratio of deionized water to carboxyl-modified PHU is 1:1 and the shearing speed is 5000 rpm. Adjust the pH of the dispersion to 8.0 and adjust the solid content to obtain a PHU aqueous dispersion with a solid content of 30 wt.%.
[0103] S5: Add pigment to a portion of the PHU aqueous dispersion, wherein the mass ratio of pigment to PHU resin solids in the portion of the PHU aqueous dispersion is 20:80, and the amount of the portion of PHU aqueous dispersion accounts for 30% of the total amount of PHU aqueous dispersion. Add wetting agent alkyl glycoside and defoamer SURFYNOL® DF-62 to obtain a color paste, wherein the amount of wetting agent added is 0.1 wt.% of the total amount of color paste, and the amount of defoamer added is 0.1 wt.% of the total amount of color paste. Add deionized water to obtain a second color paste with a solid content of 30 wt.%. Grind and disperse using a sand mill for 0.5 h to obtain a concentrated color paste; wherein the particle size of the grinding media is 0.2 mm, and the grinding temperature is 35℃.
[0104] S6: Mix the concentrated color paste with the remaining PHU aqueous dispersion, add nanocellulose dispersion, sorbitol (a humectant), wetting agent, methylisothiazolinone (a preservative), and defoamer to obtain ink, wherein the mass fraction of nanocellulose is 0.1 wt.%, the mass fraction of humectant is 2 wt.%, the mass fraction of wetting agent is 0.1 wt.%, the mass fraction of preservative is 0.01 wt.%, and the mass fraction of defoamer is 0.1 wt.%. Add cobalt-free manganese / iron drier, wherein the amount of cobalt-free manganese / iron drier is 0.1% of the ink mass. Stir at 20°C for 10 min to obtain the second ink. Adjust the pH to 8 and the solid content to 20 wt.% to obtain the biodegradable water-based ink.
[0105] Example 3
[0106] This embodiment provides a biodegradable water-based ink and its preparation method. The preparation method of the biodegradable water-based ink specifically includes the following steps:
[0107] S1: Unsaturated rapeseed oil and organic acid acetic acid were mixed at a mass ratio of 1:0.06. P-Toluenesulfonic acid was added to obtain reaction solution A, wherein the amount of p-Toluenesulfonic acid added was 0.3 wt.% of the mass of unsaturated rapeseed oil. Hydrogen peroxide solution with a mass fraction of 35 wt.% was added in batches, wherein the mass ratio of hydrogen peroxide solution to unsaturated rapeseed oil was 0.25:1. The reaction was carried out at 50℃ for 5 hours. After the reaction was completed, the mixture was washed with deionized water and neutralized to pH 6.5. The mixture was then dehydrated under reduced pressure and dried to obtain epoxidized oil.
[0108] S2: Epoxidized oil is mixed with a carbonation catalytic system to obtain reaction solution B. The carbonation catalytic system is a mixture of tetrabutylammonium quaternary ammonium salt and magnesium bromide of Lewis acid in a mass ratio of 19:1. The amount of carbonation catalytic system fed is 1.5% of the mass of epoxidized oil. Carbon dioxide is introduced and the pressure is increased to 1.5 MPa. The reaction is carried out at 90°C for 6 hours. After the reaction is completed, the temperature is reduced and the pressure is released. The product is washed, filtered, and subjected to vacuum devolatilization to obtain a cyclic carbonate precursor.
[0109] S3: A cyclic carbonate precursor, diamine A (1,6-hexanediamine), and diamine B (PEG-diamine) were mixed to obtain reaction solution C, wherein the molar ratio of diamine A to diamine B was 5:1, and the total amount of diamine A and diamine B was in a mass ratio of 15:100 to the cyclic carbonate precursor. The mixture was reacted at 60°C for 10 h to obtain PHU prepolymer. Maleic anhydride, 4-dimethylaminopyridine catalyst, and Irganox 1076 antioxidant were added to obtain reaction solution D, wherein the mass ratio of anhydride to PHU prepolymer was 10:100, the amount of catalyst was 0.2% of the mass of PHU prepolymer, and the amount of antioxidant was 0.1% of the mass of PHU prepolymer. The mixture was stirred at 80°C for 4 h to obtain carboxyl-modified PHU.
[0110] S4: Add a 0.2M arginine solution to the carboxyl-modified PHU for primary neutralization, wherein the mass ratio of arginine to carboxyl-modified PHU is 3:100. Then add a 0.2M choline hydroxide solution for secondary neutralization to obtain a neutralized solution, wherein the mass ratio of choline hydroxide to carboxyl-modified PHU is 1.2:100. Add deionized water and shear disperse for 40 min to obtain a dispersion, wherein the mass ratio of deionized water to carboxyl-modified PHU is 1.5:1 and the shearing speed is 6000 rpm. Adjust the pH of the dispersion to 8.5 and adjust the solid content to obtain a PHU aqueous dispersion with a solid content of 32 wt.%.
[0111] S5: Add pigment to a portion of the PHU aqueous dispersion, wherein the mass ratio of pigment to PHU resin solids in the portion of the PHU aqueous dispersion is 25:75, and the amount of the portion of PHU aqueous dispersion accounts for 40% of the total amount of PHU aqueous dispersion. Add wetting agent alkyl glycoside and defoamer TEGO® Foamex 832 to obtain a color paste, wherein the amount of wetting agent added is 0.15 wt.% of the total amount of color paste, and the amount of defoamer added is 0.25 wt.% of the total amount of color paste. Add deionized water to obtain a second color paste with a solid content of 40 wt.%. Grind and disperse using a sand mill for 1.0 h to obtain a concentrated color paste; wherein the particle size of the grinding media is 0.5 mm, and the grinding temperature is 38℃.
[0112] S6: Mix the concentrated color paste with the remaining PHU aqueous dispersion, add nanocellulose dispersion, propylene glycol (a humectant), wetting agent, 1,2-benzisothiazolin-3-one (a preservative), and defoamer to obtain ink, wherein the mass fraction of nanocellulose is 0.3 wt.%, the mass fraction of humectant is 6 wt.%, the mass fraction of wetting agent is 0.12 wt.%, the mass fraction of preservative is 0.05 wt.%, and the mass fraction of defoamer is 0.15 wt.%. Add cobalt-free manganese / iron drier, wherein the amount of cobalt-free manganese / iron drier is 0.2% of the ink mass. Stir at 25°C for 20 min to obtain the second ink. Adjust the pH to 8.5 and the solid content to 25 wt.% to obtain the biodegradable water-based ink.
[0113] Example 4
[0114] This embodiment provides a biodegradable water-based ink and its preparation method. The preparation method of the biodegradable water-based ink specifically includes the following steps:
[0115] S1: Unsaturated vegetable oil linseed oil and organic acid acetic acid were mixed at a mass ratio of 1:0.1. P-toluenesulfonic acid was added to obtain reaction solution A, wherein the amount of p-toluenesulfonic acid added was 0.8 wt.% of the mass of unsaturated vegetable oil. Hydrogen peroxide solution with a mass fraction of 50 wt.% was added in batches, wherein the mass ratio of hydrogen peroxide solution to unsaturated vegetable oil was 0.45:1. The reaction was carried out at 70℃ for 8 hours. After the reaction was completed, the mixture was washed with deionized water and neutralized to pH 8.0. The mixture was then dehydrated under reduced pressure and dried to obtain epoxidized oil.
[0116] S2: Epoxidized oil is mixed with a carbonation catalytic system to obtain reaction solution B. The carbonation catalytic system is a mixture of tetraethylammonium bromide (quaternary ammonium salt) and zinc bromide (Lewis acid) at a mass ratio of 15:1. The amount of carbonation catalytic system fed is 3% of the mass of epoxidized oil. Carbon dioxide is introduced and the pressure is increased to 3.5 MPa. The reaction is carried out at 130°C for 12 h. After the reaction is completed, the temperature is lowered and the pressure is released. The product is washed, filtered, and subjected to vacuum devolatilization to obtain a cyclic carbonate precursor.
[0117] S3: A reaction solution C is prepared by mixing a cyclic carbonate precursor, diamine A (1,6-hexanediamine), and diamine B (bis(3-aminopropyl) ether), wherein the molar ratio of diamine A to diamine B is 9:1, and the total amount of diamine A and diamine B is in a mass ratio of 25:100 to the cyclic carbonate precursor. The reaction is carried out at 95°C for 24 h to obtain a PHU prepolymer. Acid anhydrides succinic anhydride and itaconic anhydride, catalyst pyridine, and antioxidant Irganox 1010 are added to obtain a reaction solution D, wherein the mass ratio of acid anhydride to PHU prepolymer is 20:100, the amount of catalyst is 0.5% of the mass of PHU prepolymer, and the amount of antioxidant is 0.2% of the mass of PHU prepolymer. The reaction is carried out at 110°C for 8 h with stirring to obtain carboxyl-modified PHU.
[0118] S4: Add a 0.5M arginine solution to the carboxyl-modified PHU for primary neutralization, wherein the mass ratio of arginine to carboxyl-modified PHU is 6:100. Then add a 0.5M choline hydroxide solution for secondary neutralization to obtain a neutralized solution, wherein the mass ratio of choline hydroxide to carboxyl-modified PHU is 2:100. Add deionized water and shear disperse for 60 min to obtain a dispersion, wherein the mass ratio of deionized water to carboxyl-modified PHU is 3:1 and the shearing speed is 8000 rpm. Adjust the pH of the dispersion to 9.2 and adjust the solid content to obtain a PHU aqueous dispersion with a solid content of 40 wt.%.
[0119] S5: Add pigment to a portion of the PHU aqueous dispersion, wherein the mass ratio of pigment to PHU resin solids in the portion of the PHU aqueous dispersion is 40:60, and the amount of the portion of PHU aqueous dispersion accounts for 60% of the total amount of PHU aqueous dispersion. Add wetting agent alkyl glycoside and defoamer SURFYNOL® DF-62 to obtain a color paste, wherein the amount of wetting agent added is 0.3 wt.% of the total amount of color paste, and the amount of defoamer added is 0.3 wt.% of the total amount of color paste. Add deionized water to obtain a second color paste with a solid content of 60 wt.%. Grind and disperse using a sand mill for 2.5 hours to obtain a concentrated color paste; wherein the particle size of the grinding media is 1 mm, and the grinding temperature is 45℃.
[0120] S6: Mix the concentrated color paste with the remaining PHU aqueous dispersion, add nanocellulose dispersion, sorbitol (a humectant), wetting agent, methylisothiazolinone (a preservative), and defoamer to obtain ink, wherein the mass fraction of nanocellulose is 0.6 wt.%, the mass fraction of humectant is 12 wt.%, the mass fraction of wetting agent is 0.2 wt.%, the mass fraction of preservative is 0.1 wt.%, and the mass fraction of defoamer is 0.3 wt.%. Add cobalt-free manganese / iron drier, wherein the amount of cobalt-free manganese / iron drier is 0.5% of the ink mass. Stir at 40°C for 40 min to obtain the second ink. Adjust the pH to 9.2 and the solid content to 40 wt.% to obtain the biodegradable water-based ink.
[0121] Comparative Example 1
[0122] This comparative example provides a biodegradable water-based ink and its preparation method. The difference from Example 1 is that triethylamine is used to replace arginine and choline hydroxide in S4, while the other operation steps and process parameters are exactly the same as in Example 1.
[0123] Comparative Example 2
[0124] This comparative example provides a biodegradable water-based ink and its preparation method. The difference from Example 1 is that choline hydroxide is not added in S4, while the other operation steps and process parameters are exactly the same as in Example 1.
[0125] Comparative Example 3
[0126] This comparative example provides a biodegradable water-based ink and its preparation method. The difference from Example 1 is that S1-S4 are omitted, and commercially available water-based polyurethane is used directly. Other operating steps and process parameters are exactly the same as in Example 1.
[0127] Comparative Example 4
[0128] This comparative example provides a biodegradable water-based ink and its preparation method. The difference from Example 1 is that the full amount of PHU aqueous dispersion is directly added in S5, and the "pre-concentration of color paste followed by ink addition" is eliminated. Other operation steps and process parameters are exactly the same as in Example 1.
[0129] Comparative Example 5
[0130] This comparative example provides a biodegradable water-based ink and its preparation method. The difference from Example 1 is that nanocellulose is not added in S6, while the other operation steps and process parameters are exactly the same as in Example 1.
[0131] The performance of the biodegradable water-based inks of Examples 1-4 and Comparative Examples 1-5 was tested, and the specific process is as follows:
[0132] VOCs content test: Take each ink sample and place it in a sealed sampling bottle. After equilibration at 25℃ for 30 minutes, determine the VOCs content according to the method specified in GB / T38608-2020.
[0133] Degradability test: Take the non-volatile residue of each ink sample as the sample: prepare the residue sample by drying at 60℃ to constant weight and crushing through a 60-mesh sieve; weigh 10.0g of the sample and conduct biodegradation test under controlled aerobic composting conditions according to GB / T 19277.1-2025, with the test period set at 180 days.
[0134] Fineness test: Take each ink sample (about 5 mL) and place it on the scraper fineness meter. Use a scraper to scrape the ink at a uniform speed (scraping speed about 50 mm / s) at a specified gap. Repeat the test 3 times and take the maximum reading as the fineness value.
[0135] Viscosity test: After each ink sample is kept at 25℃ for 30 minutes, the viscosity is measured using a Zahn cup (or equivalent flow cup): Take 100 mL of ink sample and measure the time from the start of flow to the first break of the liquid flow. Repeat the test 3 times and take the average value as the viscosity.
[0136] Water resistance test: Samples of each ink were prepared on the same substrate: 80 g / m 2 Coated paper (or equivalent paper base) was coated with a 100 μm wet film thickness using a scraper and dried at 25℃ and 50%RH for 24 hours. Water resistance treatment was performed by immersion: the sample was immersed in deionized water at (25±2)℃ for 30 minutes, and after removal, the surface moisture was gently absorbed with filter paper. After standing for 10 minutes, the bubbling and color fading were observed and recorded.
[0137] The test results are shown in Table 1.
[0138] Table 1. Performance test results of biodegradable water-based inks in Examples 1-4 and Comparative Examples 1-5
[0139] VOCs content (%) Degradability (%) Fineness (μm) Viscosity (s) Water resistance Example 1 0.52 70.4 8 22 No obvious bubbling or color fading Example 2 0.49 69.6 7.9 21.8 No obvious bubbling or color fading Example 3 0.51 70 8.1 22.2 No obvious bubbling or color fading Example 4 0.50 70.1 8 22 No obvious bubbling or color fading Comparative Example 1 1.6 68 9 21 Slight color fading, no obvious bubbling Comparative Example 2 0.6 69 11 26 Slight color fading, slight bubbling Comparative Example 3 2.2 40 9 20 No obvious bubbling, slight color fading Comparative Example 4 0.50 70 12 25 Slight color fading, no obvious bubbling Comparative Example 5 0.50 70 8 15 No obvious bubbling, slight color fading
[0140] As shown in Table 1, the test results of Example 1 and Comparative Example 1 indicate that in S4, triethylamine was used to replace arginine and choline hydroxide. Since triethylamine is a volatile tertiary amine, it is more easily volatilized and included in volatile organic compounds during neutralization and ink mixing, leading to an increase in the VOCs content of the ink. At the same time, after the neutralization system changed from "amino acid salt / choline salt" to tertiary amine salt, the ion pair morphology of the dispersion, the hydration layer stability mode, and the synergistic effect of the hydrogen bond network changed. The anchoring and coating of pigments and resins were more prone to slight fluctuations, resulting in a deterioration in fineness. Tertiary amine systems often enhance the fluidity of the system, reduce the contribution of structural viscosity, and decrease viscosity. In terms of water resistance, since the pigment anchoring and film formation continuity are slightly affected, slight color migration or whitening is more likely to occur under the action of water, resulting in a decrease in overall water resistance. In terms of biodegradability, although the main resin skeleton remained unchanged, the change in the neutralization system slightly adversely affected the proportion of biodegradable components in the system and the microbial usability environment, resulting in a decrease in biodegradability.
[0141] From the test results of Example 1 and Comparative Example 2 in Table 1, it can be seen that without the addition of choline hydroxide in S4, due to the lack of alkalinity compensation and ionization window expansion brought about by co-neutralization, it is more difficult to obtain sufficiently fine and stable dispersed particles under the same pH and solid content conditions. The particles are prone to being too large or slightly flocculating, resulting in poor fineness. The coarser particles and enhanced network structure will increase the viscosity of the low-shear structure, thus increasing the viscosity. Uneven dispersion and an increase in local weak binding points will also more easily induce slight foaming or discoloration under water contact or wet rubbing conditions, resulting in decreased water resistance. Since this comparative example also did not introduce volatile tertiary amines, the overall volatility of the neutralized system is still relatively low, so the overall change in VOCs is not significant. The biodegradability is mainly determined by the PHU skeleton, and usually does not change much.
[0142] As shown in Table 1, the test results of Example 1 and Comparative Example 3 indicate that by omitting S1-S4 and directly using commercially available waterborne polyurethane, the VOC content increases. This is because commercially available waterborne polyurethane systems often contain cosolvents, residual small molecules, or low-molecular-weight components necessary in the formulation, and their salt-forming dispersion often relies on traditional amine systems. Furthermore, commercially available waterborne polyurethanes are mostly based on petrochemical-derived structures, and their main chain structure typically exhibits a lower degree of mineralization under controlled composting / aerobic conditions compared to the PHU system obtained in this application based on the ring-opening polymerization of vegetable oil and cyclic carbonates, resulting in lower biodegradability. The fineness of waterborne polyurethane dispersions decreases. Although a certain level of fineness can be achieved through grinding and dispersion, the lack of PHU for multi-point hydrogen bonding / ion anchoring synergy of pigments results in relatively insufficient stable coating efficiency and anti-reagglomeration ability after grinding, leading to a deterioration in fineness. The particle size and molecular weight distribution of commercially available waterborne polyurethane dispersions differ, resulting in a relatively low contribution of system viscosity and a decrease in viscosity. In terms of water resistance, waterborne polyurethane generally has good film-forming continuity and may not have a high risk of foaming. However, due to the different binding methods of additives and pigments in the system, the tendency for color fading / color migration under the action of water increases.
[0143] From the test results of Example 1 and Comparative Example 4 in Table 1, it can be seen that in S5, the direct addition of the full amount of PHU aqueous dispersion, eliminating the "pre-concentration of pigment paste followed by ink addition", resulted in an increase in the viscosity and elastic structure of the grinding system, a decrease in the effective shear efficiency of the grinding media, and more difficulty in dissipating foam, leading to a decrease in pigment refining efficiency and an increased risk of re-agglomeration, thus resulting in poorer fineness. At the same time, the direct participation of the full amount of resin in grinding introduces a stronger structural viscosity contribution, increasing the viscosity. Insufficient dispersion also causes uneven coating of pigment by resin and an increase in local weak binding points, making it more prone to trace color migration under water contact conditions and reducing water resistance. However, since this comparative example did not change the resin skeleton and the main additive categories, the overall level of VOCs and biodegradability did not change significantly.
[0144] As shown in Table 1, the test results of Example 1 and Comparative Example 5 indicate that without the addition of nanocellulose in S6, the system loses the reversible physical network and thixotropic structure constructed by nanocellulose, resulting in weakened shear thinning and thixotropic recovery capabilities, leading to a decrease in the viscosity of the low-shear structure. Since nanocellulose mainly plays a role in rheological regulation rather than grinding and refining, the fineness usually does not change much when the grinding conditions and resin anchoring dispersion route remain unchanged. Similarly, since the resin skeleton and the main source of small molecules have not changed, the overall level of VOCs and degradability does not change much. However, due to the lack of the inhibitory effect of the cellulose network on pigment migration and water-induced disturbance, slight color migration is more likely to occur under water contact or wet rubbing conditions, and the water resistance decreases slightly.
[0145] The above description is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in the present invention fall within the protection and disclosure scope of the present invention.
Claims
1. A method for preparing a biodegradable water-based ink, characterized in that, The preparation method includes: S1: Unsaturated vegetable oil is mixed with organic acid, p-toluenesulfonic acid and hydrogen peroxide solution are added to react, and after the reaction is completed, the mixture is washed, neutralized and dehydrated under reduced pressure to obtain epoxidized oil; S2: Epoxidized oil is mixed with a carbonation catalytic system to obtain reaction solution B. Carbon dioxide is introduced to react. After the reaction is completed, the product is washed, filtered and subjected to vacuum devolatilization to obtain a cyclic carbonate precursor. S3: A cyclic carbonate precursor, diamine A and diamine B are mixed and reacted to obtain a PHU prepolymer; an anhydride, catalyst and antioxidant are added and stirred to obtain a carboxyl-modified PHU. S4: Arginine solution is added to carboxyl-modified PHU for primary neutralization, followed by choline hydroxide solution for secondary neutralization to obtain a neutralized solution. Deionized water is added and sheared to obtain a dispersion. The pH of the dispersion is adjusted by adding arginine solution / choline solution or deionized water, and the solid content is adjusted to obtain an aqueous PHU dispersion. S5: Add pigment to part of PHU aqueous dispersion, add wetting agent alkyl glycoside and defoamer to obtain color paste, add deionized water to obtain second color paste, and use sand mill to grind and disperse to obtain concentrated color paste; S6: Mix the concentrated color paste with the remaining PHU aqueous dispersion, add nanocellulose dispersion, humectant, wetting agent, preservative and defoamer to obtain ink, add cobalt-free manganese / iron drier, stir to obtain second ink, adjust pH and solid content to obtain biodegradable water-based ink. The concentration of the arginine solution is 0.1-0.5M; The mass ratio of arginine to carboxyl-modified PHU is (1-6):100; The concentration of the choline hydroxide solution is 0.1-0.5M; The mass ratio of choline hydroxide to carboxyl-modified PHU is (1-2):100; The mass ratio of the pigment to the PHU resin solid in the PHU aqueous dispersion is (20:80)-(40:60); The amount of the PHU aqueous dispersion used accounts for 30-60% of the total amount of PHU aqueous dispersion. The ink contains 0.1-0.6 wt.% nanocellulose.
2. The method for preparing a biodegradable water-based ink according to claim 1, characterized in that, In S1: The unsaturated vegetable oil is any one of soybean oil, flaxseed oil, and rapeseed oil; The organic acid is formic acid or acetic acid; The mass ratio of the unsaturated vegetable oil to the organic acid is 1:(0.05-0.1); The amount of p-toluenesulfonic acid added is 0.1-0.8 wt.% of the mass of the unsaturated vegetable oil. The mass ratio of the hydrogen peroxide solution to the unsaturated vegetable oil is (0.15-0.45):
1.
3. The method for preparing a biodegradable water-based ink according to claim 1, characterized in that, In S2: The carbonation catalytic system is obtained by combining a quaternary ammonium salt and a Lewis acid. The mass ratio of quaternary ammonium salt to Lewis acid in the carbonation catalytic system is (15-20):
1. The quaternary ammonium salt is any one of tetrabutylammonium bromide, tetrabutylammonium chloride, tetrabutylammonium iodide, and tetraethylammonium bromide; The Lewis acid is any one of zinc bromide, zinc chloride, and magnesium bromide; The amount of feed into the carbonation catalytic system is 1-3% of the mass of the epoxidized oil.
4. The method for preparing a biodegradable water-based ink according to claim 1, characterized in that, In S3: The diamine A is any one of 1,4-butanediamine, 1,5-pentanediamine, and 1,6-hexanediamine; The diamine B is any one of 1,8-diamino-3,6-dioxane, bis(3-aminopropyl) ether, or PEG-diamine. The molar ratio of diamine A to diamine B is (1-9):1; The total amount of diamine A and diamine B fed into the cyclic carbonate precursor was in a mass ratio of (8-25):
100.
5. The method for preparing a biodegradable water-based ink according to claim 1, characterized in that, In S3: The acid anhydride is any one or more of succinic anhydride, itaconic anhydride, and maleic anhydride; The mass ratio of the acid anhydride to the PHU prepolymer is (2-20):100; The catalyst is any one of imidazole, 1-methylimidazolium, 4-dimethylaminopyridine, or pyridine. The amount of catalyst fed is 0.1-0.5% of the mass of the PHU prepolymer.
6. The method for preparing a biodegradable water-based ink according to claim 1, characterized in that, In S3: The antioxidant is any one of 2,6-di-tert-butyl-p-cresol, Irganox 1010, and Irganox 1076; The amount of antioxidant added is 0.05-0.2% of the mass of PHU prepolymer.
7. The method for preparing a biodegradable water-based ink according to claim 1, characterized in that, In S4: The mass ratio of the deionized water to the carboxyl-modified PHU is (1-3):
1.
8. The method for preparing a biodegradable water-based ink according to claim 1, characterized in that, In S5: The wetting agent alkyl glycoside is added at a rate of 0.1-0.3 wt.% of the total pigment. The defoamer is either TEGO® Foamex 832 or SURFYNOL® DF-62; The amount of defoamer added is 0.1-0.3 wt.% of the total amount of pigment.
9. The method for preparing a biodegradable water-based ink according to claim 1, characterized in that, In S6: The moisturizer is any one of glycerin, sorbitol, and propylene glycol; The humectant in the ink has a mass fraction of 2-12 wt.%; The wetting agent in the ink has a mass fraction of 0.1-0.2 wt.%; The preservative is 1,2-benzisothiazolin-3-one or methylisothiazolinone; The preservative in the ink has a mass fraction of 0.01-0.1 wt.%. The defoamer in the ink has a mass fraction of 0.1-0.3 wt.%. The amount of the cobalt-free manganese / iron drying agent added is 0.1-0.5% of the ink mass.
10. A biodegradable water-based ink prepared by the preparation method according to any one of claims 1-9.
Citation Information
Patent Citations
Preparation method and application of vegetable oil-based non-isocyanate waterborne polyurethane
CN115417987A
Non-Isocyanate Polyurethane Dispersion
US20260117025A1